Prostate-specific antigen (PSA) related to the anthropometric profile among patients admitted at the Hospital II Huamanga Carlos Tuppia García-Godos, EsSalud. Ayacucho - Gavilán Zamora, Cinthia (2021)
Objective: To determine the association between plasma and mass prostate-specific antigen (PSA) levels and the anthropometric profile, taking into account the risk of prostate pathologies. Materials and methods: A correlational, quantitative, cross-sectional and retrospective study conducted with a sample of 156 medical records of male patients with PSA tests and anthropometric data. Spearman's Rho with a 95 % confidence level was used to analyze the relationship between the variables. Results: The average age of the patients was 67.85 ± 10.83 years and their mean PSA value was 3.57 ± 7.30 ng/mL. Fifteen (15) patients (9.60 %) had a low risk (PSA = 4.1 – 9.90 ng/mL), eight (5.10 %) a medium risk (PSA = 10 – 19.90 ng/mL) and six (3.80 %) a high risk (PSA ≥ 20 ng/mL) of developing prostate pathologies. The mean body mass index (BMI) was 26.37 ± 3.81 kg/m2: 85 patients (54.50 %) were overweight and 18 (11.50 %) were obese. The mean mass PSA was 14.89 ± 30.50 μg, the body surface area (BSA) was 3.93 ± 2.72 m2 and the plasma volume was 4.18 ± 0.21 L. A very low positive correlation was evidenced between plasma PSA and age (rho = 0.184; p = 0.022) and between mass PSA and age (rho = 0.176; p = 0.028). There was a moderate positive association between plasma PSA and BSA (rho = 0.456; p = 0.000) and between mass PSA and BSA (rho = 0.463; p = 0.000). No relationship was found between BMI and PSA. Conclusions: The association between plasma and mass PSA levels and the anthropometric profile was demonstrated, taking into account the risk of prostate pathologies, which increased with BSA and age.